Tailoring electronic structure and thermodynamic stability of (Al, In)-substituted GaAs: Ab-initio insights into bulk and (001) surfaces - Arellano Ramirez, I. D. (2024)
Ab-initio calculations are conducted to investigate the structural properties, electronic structure, and thermodynamic stabilities of bulk and (001) surface systems of the GaAs semiconductor in its zinc-blende crystal phase. For the bulk case, we focus on the impact of substituting gallium atoms with M atoms (M = Al, In) at various concentrations (5.55 %, 11 %, and 22 %). We present the resulting structural parameters, along with the formation and substitutional energies associated with these substitutions. For surface systems, we explore indium (In) or aluminum (Al) substitutions at coverages of 0.25, 0.50, and 1.0 monolayers. This includes investigating the effects of substituting M atoms within the first atomic layer of the slabs. Ab-initio thermodynamic calculations reveal that high Al substitutions, in both bulk and surface, result in more favorable formation and surface energies. In contrast, In substitutions exhibit the opposite behavior, with increasing In content leading to less favorable energetics. Moreover, density of states analysis reveals that bulk systems maintained a semiconducting character, while all studied surface configurations exhibited a metallic electronic behavior. This study provides valuable insights into the influence of Al and In substitutions on the structural, electronic, and thermodynamic properties of GaAs, both in bulk and on the (001) surface.